2010
DOI: 10.1007/s11695-010-0196-x
|View full text |Cite
|
Sign up to set email alerts
|

Roux-en-Y Bypass Gastroplasty: Markers of Oxidative Stress 6 Months After Surgery

Abstract: Roux-en-Y bypass gastroplasty led to decreased proinflammatory parameters together with increased nutritional antioxidants, catalase, and TBARS, and decreased GSH 6 months after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 42 publications
(51 reference statements)
4
23
0
1
Order By: Relevance
“…Therefore, antioxidant enzymes are depleted in obesity and substrates such as GSH increase. These results corroborate the findings by Boesing et al, 35 who also found decreased GSH levels in obese patients after bariatric surgery.…”
Section: Figuresupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, antioxidant enzymes are depleted in obesity and substrates such as GSH increase. These results corroborate the findings by Boesing et al, 35 who also found decreased GSH levels in obese patients after bariatric surgery.…”
Section: Figuresupporting
confidence: 92%
“…According to Vincent and Taylor, 37 obese individuals usually consume less fruits and vegetables, which are important sources of dietary antioxidants such as ASA. This result may be confirmed by Boesing et al and Kisakol et al, 35,38 who found an inverse correlation between BMI and ASA concentrations.…”
Section: Figuresupporting
confidence: 71%
“…Reductions in inflammatory markers such as CRP and IL-6 have even been observed after weight loss as little as 5% (Imayama et al, 2012), although Madsen et al (2008) found that over a 3-year period weight loss needed to exceed 10% to induce a significant improvement in inflammatory markers. Weight loss is also associated with reduced markers of oxidative stress such isoprostane, thiobarbituric acid reactive substances and malondialdehyde (Boesing et al, 2010, Bougoulia et al, 2006, Ozcelik et al, 2005, Wycherley et al, 2008, and increased antioxidant enzymes such as glutathione peroxidase and catalase (Boesing et al, 2010, Bougoulia et al, 2006.…”
Section: Does Weight Loss Improve Dysregulated Pathways Associated Wimentioning
confidence: 99%
“…We identified 15 studies investigating the effect of weight loss interventions (diet- and/or exercise-, and surgery-induced) on individuals' oxidative stress level (table 1): 6 RCTs and 9 non-randomized intervention studies (n = 5 diet, n = 6 diet and/or exercise interventions, and n = 3 bariatric surgery interventions) [35,36,37,38,39,40,41,42,43,44,45,46,47,48]. All studies measured oxidative stress markers in blood samples (plasma or serum, e.g., enzyme activities, 8-isoprostane, 8-oxo-dG; for details see table 1) [35,36,37,38,39,40,41,42,43,44,45,46,47,48].…”
Section: Resultsmentioning
confidence: 99%
“…All studies measured oxidative stress markers in blood samples (plasma or serum, e.g., enzyme activities, 8-isoprostane, 8-oxo-dG; for details see table 1) [35,36,37,38,39,40,41,42,43,44,45,46,47,48]. …”
Section: Resultsmentioning
confidence: 99%